Chitosan Nanoparticles Enhance the Antiproliferative Effect of Lapachol in Urothelial Carcinoma Cell Lines - Tatiane Roquete Amparo; Kamila de Fátima da Anunciação; Tamires Cunha Almeida; Lucas Resende Dutra Sousa; Viviane Flores Xavier; Janaína Brandão Seibert; Ana Paula Moreira Barboza; Paula Melo de Abreu Vieira; Orlando David Henrique dos Santos; Glenda Nicioli da Silva; Geraldo Célio Brandão (Pharmaceutics, 2025)
Backgroud/Objectives: Lapachol is a naturally occurring prenylated naphthoquinone with antiproliferative effects. However, its clinical application remains limited due to several factors, including poor water solubility, low bioavailability, and adverse effects. The development of chitosan-based nanoparticles holds promise in overcoming these challenges and has emerged as a potential nanocarrier for cancer therapy, including bladder cancer. The objective of this study was to develop and evaluate the effects of chitosan nanoparticles on bladder tumor cell lines. Methods: The nanoemulsion was prepared using the hot homogenization method, while the chitosan nanoparticles were obtained through the ionic gelation technique. The nanoformulations were characterized in terms of particle size and polydispersity index (PDI) using photon correlation spectroscopy, and zeta potential by electrophoretic mobility. Encapsulation efficiency was determined by ultracentrifugation, and the drug release was analyzed using the dialysis method. The antineoplastic potential was assessed using the MTT assay, and the safety profile was assessed through ex vivo analysis. Cellular uptake was determined by fluorescence microscopy. Results: The study demonstrated that both the chitosan-based nanoemulsion and nanospheres encapsulating lapachol exhibited appropriate particle sizes (around 160 nm), high encapsulation efficiency (>90%), and a controlled release profile (Korsmeyer–Peppas model). These nanoemulsion systems enhanced the antiproliferative activity of lapachol in bladder tumor cells, with the nanospheres showing superior cellular uptake. Histopathological analysis indicated the safety of the formulations when administered intravesically. Conclusions: The results suggest that chitosan nanoparticles may represent a promising alternative for bladder cancer treatment.